Analisis Beban Kerja Mental Personel Industrial Hygiene Menggunakan Metode NASA-TLX di PT X - Revika (Journal of Industrial Innovation and Safety Engineering (JINSENG), 2026)
Mental workload is a critical factor influencing worker performance and safety in the oil and gas industry. The high demands placed on Industrial Hygiene personnel have the potential to cause mental fatigue, which can negatively affect work effectiveness. This study aims to analyze the level of mental workload among Industrial Hygiene personnel at PT X using the NASA‑TLX method. This method was chosen because it measures workload multidimensionally through six key indicators, making it more comprehensive compared to traditional measurement approaches. Data were collected using NASA‑TLX questionnaires, processed into workload scores, and analyzed based on workload dimensions. The results indicate that mental demand and temporal demand dimensions scored the highest, highlighting significant pressure on cognitive and time-related aspects of work. These findings suggest the need for strategies to control mental workload in order to maintain worker health and productivity.